1979
DOI: 10.3109/03005367909078883
|View full text |Cite
|
Sign up to set email alerts
|

External Electrical Stimulation of the Cochlea: Clinical, Psychophysical, Speech-Perceptual and Histological Findings

Abstract: Our progress towards the development of a particular form of cochlear implant for the totally deaf is described. A single channel stimulation at the round window or promontory is used. This involves a minimum of surgical intervention and infective risk, preserves the possibility of remission and allows the application of later developments. The signal used for stimulation is designed to be matched both to the deaf lip-reader's needs and to his new, restricted, auditory ability. This is done by concentrating on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1
3

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 5 publications
3
31
1
3
Order By: Relevance
“…This range corresponds approximately to the F0 frequency range for many (but not all) speakers, and for other complex sounds such as those produced by certain musical instruments. Similar reasoning supported the development of an early single-channel extra-cochlear prosthesis (Fourcin et al, 1979), which was intended primarily as a speech-reading aid. That device also applied stimulation to the auditory nerve at a frequency derived from an estimate of F0.…”
Section: Feature-extracting Strategiesmentioning
confidence: 70%
“…This range corresponds approximately to the F0 frequency range for many (but not all) speakers, and for other complex sounds such as those produced by certain musical instruments. Similar reasoning supported the development of an early single-channel extra-cochlear prosthesis (Fourcin et al, 1979), which was intended primarily as a speech-reading aid. That device also applied stimulation to the auditory nerve at a frequency derived from an estimate of F0.…”
Section: Feature-extracting Strategiesmentioning
confidence: 70%
“…The range of currents between the detection threshold and the point at which an uncomfortable sensation occurs can be very small and is typically in the range 3 to 20 dB (27,28). This is much less than the dynamic range of acoustic hearing, which is approximately 120 dB (16).…”
Section: Coding In Cochlear Implantsmentioning
confidence: 99%
“…Experiments with animals suggest that phase locking to electric stimuli is very precise (25,67), so one might expect that frequency could be represented very precisely in the pattern of phase locking. In practice, people with cochlear implants show a rather poor ability to detect changes in the periodicity of the electric waveform applied to a single electrode, and most cannot discriminate changes at all for repetition rates above approximately 300 Hz (27,28).…”
Section: Coding In Implantsmentioning
confidence: 99%
“…These changes have been shown to be powerful cues to accent perception in Dutch speech (Cohen & t'Hart, 1967). Cues to the location of stressed syllables in English have also been investigated: various workers have demonstrated that pitch is a sufficient cue for the perception of stress (Bolinger, 1958;Faure, Hirst, & Chafcouloff, 1980;Fourcin, Rosen, Moore, Douek, Clarke, Dodson, & Bannister, 1979;Fry, 1958;Lieberman, 1960;Morton & Jassem, 1965). In view of the perceptual salience of these changes in speech, Thomassen argued that there was no reason why they should be less effective in music.…”
mentioning
confidence: 99%